E-006 Intraprocedural flat panel perfusion scan-immediate reversal of deficit after MCA thrombectomy. (4th July 2012) - Moser, F; Maya, M; Moore, T; Song, S; Pressman, B
Abstract : Purpose: Flat Panel Detector CT (FPCT) has shown promise as a tool in treating and assessing acute stroke treatment. 1–3 We have begun are organized study to compare this modality to standard multislice CT perfusion studies and see if reversal of prediction of outcomes can be derived from these intraprocedural studies. We are reporting our initial experience. Case: A 58-year-old male was transferred to our institution after being given intravenous t-PA for an acute left middle artery stroke. On admission he was nearly completely recovered from his event with a CTA demonstrating a defect in the left distal M1 segment. On hospital day 2 he developed a profound left-sided weakness. A MSCT perfusion showed a large perfusion deficit in the right MCA territory with an occlusion of the artery on the CTA. He was brought to the angiographic suite and was entered into an IRB approved post marketing study of FPCT perfusion. He underwent an aortic run with the catheter in the very proximal aorta before (Abstract E-006 figure 1 ) and after (Abstract E-006 figure 2 ) successful thrombectomy with a 054 Penumbra System. Results: The FPCT perfusion study demonstrated immediate reversal of the perfusion deficit and the patient recovered. We will present the studies. Conclusion: Although this is an initial case there was a dramatic change in the perfusion scan and rapid clinical improvement. The study is ongoing. Competing interests: F Moser: None. M Maya: None. T Moore: Siemens Medical Solutions. S Song: None. B Pressman: None. References: 1. Struffert T, Deuerling-Zheng Y, Kloska S, et al. Flat panel detector CT in the evaluation of brain parenchyma, intracranial vasculature, and cerebral blood volume: a pilot study in patients with acute symptoms of cerebral ischemia. AJNR Am J Neuroradiol 2010;31 :1462–9. 2. Struffert T, Deuerling-Zheng Y, Engelhorn T, et al. Feasibility of Cerebral Blood Volume Mapping by Flat Panel Detector CT in the Angiography Suite: First Experience in Patients with Acute Middle Cerebral Artery Occlusions. 10.3174/ajnr.A2839. 3. Mordasini P, El-Koussy M, Brekenfeld C, et al. Applicability of tableside flat panel detector CT parenchymal cerebral blood volume measurement in neurovascular interventions: preliminary clinical experience. AJNR 2012;33 :154–8.